The theatre methodology for facilitating discussion in human-robot interaction on information disclosure in a home environment - Otero, Nuno (2011)
Our research is concerned with developing scenarios for robot home companions as part of the EU project LIREC. In this work, we employed a particular methodology to gain user feedback in early stages of robot prototyping: the Theatre HRI (THRI) methodology which we have recently introduced in a pilot study. Extending this work, this study used a theatre presentation to convey the user experience of domestic service robots to a group of participants and to gain their feedback in order to further refine our scenarios. The play was designed both from the perspective of projected technological development of the LIREC project, as well as for facilitating engagement with an audience of secondary school students. At the end of the play the audience was involved in a discussion regarding issues such as acceptability of the scenario and the intrahousehold disclosure of information by the robot. Findings suggest that this methodology was effective in eliciting discussion with the audience and that problems related to intra-household disclosure of information were best resolved by clear-cut solutions tied to ownership and clear principles.